Caring supporters or daring usurpers? Representation of women in Akan proverbs - Diabah, G.; Appiah Amfo, N.A. (Discourse and Society, 2014)
The article examines the representation of women as espoused in a number of Akan (Niger-Congo, Kwa) proverbs. The objective is to analyze traditional views on the perceptions and roles of the woman in Akan society and explore the interrelation between language, gender and culture. Using a (Feminist) Critical Discursive Approach, 62 Akan proverbs about women, selected from both written and oral sources, are examined. We argue that although the contexts within which these proverbs are used may not always be gendered, by focusing on women (and men), Akans tend to present women in particular stereotypical ways through the use of these gendered proverbs, most of which can be interpreted as derogatory, negative or subservient. We also argue that although women are sometimes represented positively, such representations, which are seen as virtues, often lure them into accepting and playing these traditional stereotyped roles, thus reinforcing hegemonic masculinity and femininity. © The Author(s) 2014.
Keywords: Africa; Akan; culture; Feminist Critical Discourse Analysis; gender; gender roles; Ghana; hegemonic femininity; hegemonic masculinity; patriarchy; proverbs; representation; stereotypes; women